PENINGKATAN PROFESIONALISME TENAGA KEPENDIDIKAN DI MTs PONDOK KARYA PEMBANGUNAN AL-HIDAYAH KOTA JAMBI - Nur Indahsari; M. Amin Jamaluddin; Syamsul Huda (JMiE (Journal of Management in Education), 2020)
This research aims to describe the improvement of the professionalism of education personnel in MTs Pondok Karya Pembangunan (PKP) Al-Hidayah Jambi City. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results showed the improvement of the professionalism of education personnel in MTs PKP Al-Hidayah implemented through training programs for staff / employees in training, providing course facilities for staff / employees to improve performance in the field of administration. The activity is an effort to develop, brief knowledge, and skills of attitudes and behaviors of staff / employees to be able to meet the needs both now and in the future.